Effects of magnesium deprivation on development and biomineralization in the sea urchin Arbacia lixula. Issue 3 (3rd July 2019) - Martino, Chiara; Chiarelli, Roberto; Roccheri, Maria Carmela; Matranga, Valeria; Byrne, Maria
ABSTRACT: Echinoderms have an extensive endoskeleton composed of magnesian calcite and occluded matrix proteins. As biomineralization in sea urchin larvae is sensitive to the Magnesium:Calcium ratio of seawater, we investigated the effects of magnesium deprivation on development and skeletogenesis in the sea urchin Arbacia lixula . We focused on the localization of the skeletogenic cells (primary mesenchyme cells) and the spatial expression of associated genes. Embryos reared in Mg-free seawater exhibited developmental delay from 6-h post-fertilization and at 24 h embryos showed complete lack of biomineral formation. Larvae (48–72 h) exhibited severe skeleton malformations. Fluorescent labelling revealed that the primary mesenchyme cells and the developing skeleton of treated embryos were in an abnormal ectopic location. Expression of the skeleton matrix protein gene ( msp130 ) in the primary mesenchyme cells as seen using in situ hybridization was normal at 24 h. At 48 h this gene was down-regulated in control larvae, but not in treated larvae. Development of the pigment cells, immune cells that, like the skeleton, are mesodermal derivatives, was also impaired. Our results highlight the essential role of Mg in skeleton formation in sea urchin embryos with an indication that this element is also generally important for the development of mesoderm. Abbreviations: hpf: hours post fertilization; PMCs: primary mesenchyme cells; ACC: amorphous calcium carbonate; MgFSW: magnesium-free seawater; FSW: filtered seawater Impact statement Echinoderms have an extensive endoskeleton composed of magnesian calcite We investigated the effects of magnesium deprivation on development and skeletogenesis in the sea urchin Arbacia lixula Magnesium deprivation caused developmental delay and skeleton malformations Primary mesenchyme cells of treated embryos were in an abnormal ectopic location The spatial and temporal expression profile of the skeleton matrix protein gene ( msp130 ) was found to be different from controls Our results highlight the essential role of Mg across developmental processes in sea urchin embryos.